Validation of the French Version of the Yale Food Addiction Scale: An Examination of its Factor Structure, Reliability, and Construct Validity in a Nonclinical Sample. (May 2014) - Brunault, Paul; Ballon, Nicolas; Gaillard, Philippe; Réveillère, Christian; Courtois, Robert
Objective: The concept of food addiction has recently been proposed by applying the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision, criteria for substance dependence to eating behaviour. Food addiction has received increased attention given that it may play a role in binge eating, eating disorders, and the recent increase in obesity prevalence. Currently, there is no psychometrically sound tool for assessing food addiction in French. Our study aimed to test the psychometric properties of a French version of the Yale Food Addiction Scale (YFAS) by establishing its factor structure and construct validity in a nonclinical population. Method: A total of 553 participants were assessed for food addiction (French version of the YFAS) and binge eating behaviour (Bulimic Investigatory Test Edinburgh and Binge Eating Scale). We tested the scale's factor structure (factor analysis for dichotomous data based on tetrachoric correlation coefficients), internal consistency, and construct validity with measures of binge eating. Results: Our results supported a 1-factor structure, which accounted for 54.1% of the variance. This tool had adequate reliability and high construct validity with measures of binge eating in this population, both in its diagnosis and symptom count version. A 2-factor structure explained an additional 9.1% of the variance, and could differentiate between patients with high, compared with low, levels of insight regarding addiction symptoms. Conclusions: In our study, we validated a psychometrically sound French version of the YFAS, both in its symptom count and diagnostic version. Future studies should validate this tool in clinical samples.